Stable angina: current guidelines and advances in management. Issue 17 (9th September 2013) - Shah, Anoop; Fox, Keith
Abstract: Our Drug Review discusses the current recommended management of stable angina, focussing on secondary prevention and the control of symptoms, followed by sources of further information and an analysis of prescription data.